Cancer-associated fibroblasts promote progression and gemcitabine resistance via the SDF-1/SATB-1 pathway in pancreatic cancer. Issue 11 (November 2018) - Wei, Lusheng; Ye, Huilin; Li, Guolin; Lu, Yuanting; Zhou, Quanbo; Zheng, Shangyou; Lin, Qing; Liu, Yimin; Li, Zhihua; Chen, Rufu
Abstract Cancer-associated fibroblasts (CAFs), a dominant component of the pancreatic tumor microenvironment, are mainly considered as promotors of malignant progression, but the underlying molecular mechanism remains unclear. Here, we show that SDF-1 secreted by CAFs stimulates malignant progression and gemcitabine resistance in pancreatic cancer, partially owing to paracrine induction of SATB-1 in pancreatic cancer cells. CAF-secreted SDF-1 upregulated the expression of SATB-1 in pancreatic cancer cells, which contributed to the maintenance of CAF properties, forming a reciprocal feedback loop. SATB-1 was verified to be overexpressed in human pancreatic cancer tissues and cell lines by quantitative real-time PCR, western blot, and immunohistochemical staining, which correlated with tumor progression and clinical prognosis in pancreatic cancer patients. We found that SATB-1 knockdown inhibited proliferation, migration, and invasion in SW1990 and PANC-1 cells in vitro, whereas overexpression of SATB-1 in Capan-2 and BxPC-3 cells had the opposite effect. Immunofluorescence staining showed that conditioned medium from SW1990 cells expressing SATB-1 maintained the local supportive function of CAFs. Furthermore, downregulation of SATB-1 inhibited tumor growth in mouse xenograft models. In addition, we found that overexpression of SATB-1 in pancreatic cancer cells participated in the process of gemcitabine resistance. Finally, we investigated the clinical correlations between SDF-1 and SATB-1 in human pancreatic cancer specimens. In summary, these findings demonstrated that the SDF-1/CXCR4/SATB-1 axis may be a potential new target of clinical interventions for pancreatic cancer patients.